Comparative analysis of 6-0 nylon and 6-0 vicryl rapide in congenital unilateral cleft lip repair - J K Dayashankara Rao; Payal Luthra; Varun Arya; Vijay Siwach; Anil Sheorain; Priyanka Mudgal (Wolters Kluwer Medknow Publications, 2016)
Context: The type of suture material used in surgery has been a long standing debate among surgeons. In this study we compared rapidly absorbable suture material (Vicryl Rapide TM or Irradiated Polygalactin 910) with non-absorbable suture material (Nylon or Polyamide) in patients with nonsyndromic congenital unilateral cleft lip. Aims: To compare the appearance and course of scar, wound infection and patient's parent perception between the two groups. Settings and Design: Randomized prospective controlled study. Methods and Material: 20 patients, in the age group of 3-18 months were randomly allocated to two groups with 10 patients each. Skin suturing was done with 6-0 Polyamide and 6-0 Irradiated polygalactin the respective groups. Patients were evaluated at 1 week, 1 month, 3 months, 6 months and 1 year postoperatively by the observer as well as by the patient's parent. Results and Conclusion: It was found that Vicryl Rapide showed poorer cosmetic outcomes regarding height and pigmentation of scar as compared to nylon sutures.However, this sample size and follow-up period is very small to generalize these findings.